Developing “Games Card Bathaqo” Media in Learning Arabic Language for Fifth-Grade Students at Muhammadiyah Elementary School Pepe Bantul Yogyakarta - Abdul Azis (Lughawiyah: Journal of Arabic Education and Linguistics, 2026)
Vocabulary is vital in learning Arabic. Using good Arabic learning media will improve the quality of learning outcomes, including increasing and strengthening vocabulary memorization. This study aimed to develop games card-based Arabic learning media for fifth-grade elementary school students. The research used the R & D method developed by Sugiyono. Collecting data in this study used several techniques: observation, questionnaires, and interviews. Meanwhile, the data analysis techniques used were qualitative analysis techniques and quantitative analysis techniques. Qualitative analysis techniques were used to analyze the results of the experts' reviews, product trial results, and usage trials; which contained input, responses, suggestions, and criticisms. And quantitative analysis techniques were used to analyze the data that had been collected. The results of this study produced games card media products for learning Arabic. This product contains Arabic vocabulary material for fifth-grade students. This research showed that the games card media that had been developed was valid by media experts and material experts, as evidenced by the validation results of media experts of 95.5% and material experts of 98.3%. The feasibility of media games cards in learning Arabic is also based on the results of product trials and usage trials. at the product trial stage with test subjects from students totaling twelve students, this gave a value of 85.5% and in the usage trial obtained a value of 78.8%. From this value, it can be said that students agree with the learning media games card to improve Arabic vocabulary at Muhammadiyah Pepe Bantul Yogyakarta developed is worthy of good criteria. The response from the test subjects is in accordance with the results of validation conducted by media experts and material expert.